Application of Gene Editing for Climate Change in Agriculture - Karavolias, Nicholas G.; Horner, Wilson; Abugu, Modesta N.; Evanega, Sarah N. (Frontiers in Sustainable Food Systems, 2021)
Climate change imposes a severe threat to agricultural systems. Efforts in crop and livestock gene editing have been undertaken to improve performance across a range of traits. Many of the targeted phenotypes include attributes that could be beneficial for climate change adaptation. Here, we present examples of emerging gene-editing applications and research initiatives that are targeted to the improvement of crops and livestock in response to climate change, and discuss technical limitations and opportunities therein. While only few applications of gene editing have been translated to agricultural production thus far, numerous studies in research settings have demonstrated the potential for potent applications to address climate change in the near future.